KEDUDUKAN PURCHASE ORDER DALAM KONSTRUKSI HUKUM PERJANJIAN DI INDONESIA - Eva Juliana (2023)
The absence of legal regulations and contradictions between judge decisions relating to purchase orders causes a dilemma regarding the position of purchase orders in the construction of law in Indonesia. The paper was written to know the position of purchase order documents in the construction of contract law in Indonesia and to determine the legal consequences of a breach of a purchase order. This paper used a normative juridical method, with statute and case approaches to approach the problems. Based on the study results, a purchase order can be recognized as an agreement if the document meets the required elements to be a legally enforceable contract signed by all parties. Next to it, the breach of a purchase order is an act of default, and the parties can resolve it through litigation or non-litigation dispute resolution. The aggrieved party can use a purchase order as evidence to settle the contract default, but a purchase order document is a weak evidence. Based on that, it would be better if the parties made a sale agreement with the authorized officials to complement the purchase order document, so there would be perfect evidence if something terrible happened to the deal in the future.